A Peer-tutoring Model as Support to Autonomous English Learning - Viáfara González, John Jairo; Ariza Ariza, Judith Aleida (Íkala, Revista de Lenguaje y Cultura, 2008)
This article presents the phases of diagnosis, planning and implementation of a tutoring model which supports autonomous learning in language students at a public university in Colombia. The research process permitted us to outline the design of the basic principles in peer-tutoring, the profile of the student–tutor and the model of the tutoring process to be implemented at a later stage. Received: 19-11-07 /Accepted: 27-02-08 How to reference this article: Viafara Gonzalez, J. J. & Ariza Ariza, J. A. (2008). Un modelo tutorial entre compañeros como apoyo al aprendizaje autónomo del inglés. Íkala. 13(1), pp.173-209